Controlled Laser-Induced Oxidation Marking for Submillimeter Unique Identification Tags Based on X-Ray Fluorescence - Xiashuang Li; Weiping He; Lei Lei; Gaifang Guo; Tengyun Zhang; Ting Yue; Ling Huang (IEEE Photonics Journal, 2016)
In this paper, a comprehensive study of controlled laser-induced oxidation marking, which is used as a reliable solution to submillimeter unique identification, is conducted. The experimental statistics indicate that the recognition method for submillimeter unique identification tags is reproducible. The size of tags could be precisely controlled and minimized to $0.5× 0.5\ \text{mm}^{2}$ . Different laser-induced oxidation modules are obtained and divided into 15 groups for different tags. In addition, it is found that module oxidation increases with laser power and decreases with $Q$ frequency, scan speed, and hatch spacing. However, the sensitivity of oxidation to laser parameter differs for different oxidation modules. Even so, the reproducibility and stability of the method are valid by properly limiting deviation of the laser parameters. The aging test reveals that the detected results of the laser-induced oxidation modules are stable in a natural corrosion environment, and applying a transparent coating based on polyester polyurethane on the tags can ensure durability in a severe corrosion environment. The fabricated submillimeter unique identification tags, which can be read reliably by an X-ray fluorescence scanner, show that the proposed marking method is convenient and efficient with high repeatability and controllability.